Micrometric Observations on the Large Intestine of Goat Kids ( - Prakash, Ajay; Chandra, G; Farooqui, M M; Pathak, Archana (Indian Journal of Veterinary Anatomy, 2012)
Caecum, colon and rectum were studied in 16 apparently healthy goat kids divided in to precolostral, colostral fed, milk fed and fodder fed groups. In all the groups, the average thickness of the mucosa was maximum (498.71±51.5μ) in the colon of milk fed kids. The average height of the epithelium was maximum (34.25±2.28 μ) in the rectum of colostral fed kids. The maximum average diameter of the intestinal gland was 70.79±3.51 μ in the caecum of the milk fed kids.